Wpływ sposobu finansowania wydatków rządowych na oddziaływanie polityki fiskalnej. Ujęcie modelowe - Krajewski, Piotr (Gospodarka w Praktyce i Teorii, 2011)
The impact of a government spending financing is analysed in the article. The analysis is based on Baxter and King real business cycle model. It occurred that the choice of the financing method of a government spending is crucial for the impact of the fiscal policy on the economy. The increase in a government spending financed by budget deficit decreases consumption and leisure time and increases the level of labour and production. On the contrary the increase in a government spending financed by higher taxes depended on production has a significant negative impact on GDP.